Pengembangan Instrumen Penilaian Afektif Berbasis Self Assesment pada Materi Biodiversity Kelas X di SMA Negeri 9 Medan - Nainggolan, Farizah Handayani; Djulia, Ely; Hasairin, Ashar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to develop an affective assessment instrument based on self-assessment of biodiversitymaterial class X at SMA Negeri 9 Medan. This research uses research methods used to produce certain products and test the validity and practicality of products with the Thiagarajan development model (4D) which consists of 4 stages of development, namely define, design, develop and disseminate. The subject of this study is class X at SMA Negeri 9 Medan which consists of 108 students. This research focuses on the affective realm of science, namely in the form of scientific attitudes, which include indicators of curiosity, objectivity, cooperation, responsibility, open thinking, and discipline. This development stage consists of instrument validation, reliability analysis and instrument testing. The results of the study showed that (1) after being validly tested with an average value of 3.52 with the category of very feasible using SPSS data. (2) Viewed as a whole from the Alpha Cronbach coefficient, it can be concluded that the assessment device is declared reliable on the high reliability criteria because the test scores in classes X1, X2, and X3 are 0.821, 0.821, and 0.836. (3) The results of the trial that have been carried out are concluded that the effectiveness criteria have been achieved with the average score of the three respondents being 82%.